Vaccine-associated enhanced disease in humans and animal models: Lessons and challenges for vaccine development - Bigay, Julie; Le Grand, Roger; Martinon, Frédéric; Maisonnasse, Pauline (Frontiers in Microbiology, 2022)
The fight against infectious diseases calls for the development of safe and effective vaccines that generate long-lasting protective immunity. In a few situations, vaccine-mediated immune responses may have led to exacerbated pathology upon subsequent infection with the pathogen targeted by the vaccine. Such vaccine-associated enhanced disease (VAED) has been reported, or at least suspected, in animal models, and in a few instances in humans, for vaccine candidates against the respiratory syncytial virus (RSV), measles virus (MV), dengue virus (DENV), HIV-1, simian immunodeficiency virus (SIV), feline immunodeficiency virus (FIV), severe acute respiratory syndrome coronavirus 1 (SARS-CoV-1), and the Middle East respiratory syndrome coronavirus (MERS-CoV). Although alleviated by clinical and epidemiological evidence, a number of concerns were also initially raised concerning the short- and long-term safety of vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which is causing the ongoing COVID-19 pandemic. Although the mechanisms leading to this phenomenon are not yet completely understood, the individual and/or collective role of antibody-dependent enhancement (ADE), complement-dependent enhancement, and cell-dependent enhancement have been highlighted. Here, we review mechanisms that may be associated with the risk of VAED, which are important to take into consideration, both in the assessment of vaccine safety and in finding ways to define models and immunization strategies that can alleviate such concerns.